The Function of the Selametan Tradition in Forming Social Cohesiveness - Syntia Maharani (FISIP UIN SGD Bandung, 2021)
This study aims to understand the function of the Selametan Tradition for the people of Utan Kramat Batok Village, Cabangbungin District, Bekasi Regency. It also aims to know the process of forming social cohesiveness in the tradition of salvation in the people of that area. This study uses a qualitative descriptive method that describes and explains the field. Using observational data collection techniques, in-depth interviews, documentation, and literature studies in the village of Utan Kramat Batok. The data analysis was carried out using qualitative data analysis. The research results show that the Selamatetan tradition has many functions and great benefits for the life of the Utan Kramat Batok community, such as maintaining friendly relations between villagers, creating social solidarity, cooperation, and other benefits when the Selamatetan Tradition is taking place. The process of forming social cohesiveness in the Selametan Tradition in the Utan Kramat Batok community, occurs when the Selametan tradition takes place, because a social group comes together and meets with one another's social groups between individuals with groups, groups with groups and individuals with individuals become one so that creating a sense of group, brotherhood or usability.